Pneumococcal Infection among Children before Introduction of 13-Valent Pneumococcal Conjugate Vaccine, Cambodia - Paul Turner; Claudia Turner; Kuong Suy; Sona Soeng; Sokeng Ly; Thyl Miliya; David Goldblatt; Nicholas P.J. Day (Emerging Infectious Diseases, 2015)
Vaccination of children with pneumococcal conjugate vaccine (PCV13) was initiated in Cambodia in 2015. To determine baseline data, we collected samples from children in 2013 and 2014. PCV13 serotypes accounted for 62.7% of colonizing organisms in outpatients and 88.4% of invasive pneumococci overall; multidrug resistance was common. Thus, effectiveness of vaccination should be high.